2019
DOI: 10.1021/acsnano.9b01993
|View full text |Cite
|
Sign up to set email alerts
|

Transient Photoinactivation of Cell Membrane Protein Activity without Genetic Modification by Molecular Hyperthermia

Abstract: Precise manipulation of protein activity in living systems has broad applications in biomedical sciences. However, it is challenging to use light to manipulate protein activity in living systems without genetic modification. Here, we report a technique to optically switch off protein activity in living cells with high spatiotemporal resolution, referred to as molecular hyperthermia (MH). MH is based on the nanoscale-confined heating of plasmonic gold nanoparticles by short laser pulses to unfold and photoinact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 80 publications
1
42
0
Order By: Relevance
“…MH selectively inactivates enzymes targeted by AuNS and leaves untargeted enzymes intact, demonstrating the spatial selectivity of MH [25,27]. We further showed that MH can be used to inactivate cell membrane proteins in live cells without compromising cell viability [26]. MH is a promising method to selectively and remotely manipulate protein activity and cellular behavior.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…MH selectively inactivates enzymes targeted by AuNS and leaves untargeted enzymes intact, demonstrating the spatial selectivity of MH [25,27]. We further showed that MH can be used to inactivate cell membrane proteins in live cells without compromising cell viability [26]. MH is a promising method to selectively and remotely manipulate protein activity and cellular behavior.…”
Section: Introductionmentioning
confidence: 77%
“…GPCRs is a large protein family and contains many potential drug targeting sites for disease treatments. In our previous study, we have investigated protease activated receptor 2 (PAR2), which is also a GPCR [26]. Although kinetic parameters vary from protein to protein, impact zones of opsin and related receptors suggest MH can be a useful method to inactivate GPCRs.…”
Section: Effect Of Thermal Interfacial Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Heating generated by nanomaterials broadly falls into one of two regimes: nanoscale-confined heating (NCH) and macroscale-collective heating (MCH). NCH is characterized by local temperature increases at the nanoscale which remain confined near the surface of the nanoparticle, as in the case of controlling protein activity by molecular hyperthermia, [15,16,26] or membrane permeability by opto-poration. [16,[26][27][28] In contrast, MCH is characterized by a widespread temperature increase throughout the medium, such as whole cells or tissues.…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena have been harnessed for a variety of applications. For example, near-field enhancement can be used for optical trapping of molecules 4 , while surface-enhanced Raman scattering and photothermal effects have found applications in imaging 5, 6 , sensing 7, 8, 9, 10 and actuation of biological activities 11, 12 . However, nanoparticles subjected to pulsed laser irradiation may also undergo laser-induced fragmentation, in which the original nanoparticles are fragmented into smaller particles 13 .…”
mentioning
confidence: 99%